THE EVALUATION OF DIFFERENT THERAPIES IN THE PATIENTS WITH HELICOBACTER PYLORI - Ali ÖZDEN; Ömer DÖNDERİCİ and Şükrü DUMLU and F. IŞITAN and Hülya ÇETİNKAYA and Özden UZUNALİMOĞLU (Turkish Journal of Gastroenterology, 2020)
-